2018
DOI: 10.1007/s00253-018-9059-5
|View full text |Cite
|
Sign up to set email alerts
|

Fatty acid synthesis pathway provides lipid precursors for rhamnolipid biosynthesis in Burkholderia thailandensis E264

Abstract: Rhamnolipid production was monitored for a period of 216 h using different substrates in Pseudomonas aeruginosa PAO1 and Burkholderia thailandensis E264 which showed comparable crude yields attained by both after 216 h. The crude yield for P. aeruginosa, however, was significantly higher at the early stages of fermentation (72 or 144 h). Additionally, P. aeruginosa produced rhamnolipid with odd and even carbon chain lipid moieties using odd carbon chain fatty acid substrates (up to 45.97 and 67.57%, respective… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
16
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
7
1

Relationship

2
6

Authors

Journals

citations
Cited by 23 publications
(18 citation statements)
references
References 31 publications
2
16
0
Order By: Relevance
“…More new odd chain lengths are C 11 -C 14 , C 11 -C 14:1 , C 12 -C 13 , C 10 -C 15:1 , C 13 -C 13 , C 12 -C 15 , C 13 -C 14:1 , and C 13 -C 16 . For the third category, it has to be mentioned that other odd chain lengths were detected earlier (30,37,51). In our results, it is striking that 7.7% of the overall congeners are new congeners with odd numbers synthesized by E. coli C43(DE3) pAMB.…”
Section: Figsupporting
confidence: 53%
“…More new odd chain lengths are C 11 -C 14 , C 11 -C 14:1 , C 12 -C 13 , C 10 -C 15:1 , C 13 -C 13 , C 12 -C 15 , C 13 -C 14:1 , and C 13 -C 16 . For the third category, it has to be mentioned that other odd chain lengths were detected earlier (30,37,51). In our results, it is striking that 7.7% of the overall congeners are new congeners with odd numbers synthesized by E. coli C43(DE3) pAMB.…”
Section: Figsupporting
confidence: 53%
“…The non-pathogenic bacterium B. thailandensis is a promising candidate for the production of rhamnolipids (Dubeau et al, 2009;Funston et al, 2016;Irorere et al, 2018;Kourmentza et al, 2018). However, current yields remain low.…”
Section: Discussionmentioning
confidence: 99%
“…BS naturally play a major role in bioremediation following oil spills and act as efficient dispersing agents facilitating microbial biodegradation (De Almeida et al 2016 ; Franzetti et al 2010 ). Despite their versatile properties, a higher production cost compared to chemical surfactants and the pathogenicity of some BS producing strains, remain a major obstacles for their large-scale production (Irorere et al 2018 ) and the search for non-pathogenic strains remain an important research area (Elshikh et al 2017 ; Funston et al 2016 ). Therefore, an important question to address before they can achieve widespread application is “can we develop a cost-effective and ecologically benign process for BS production?”…”
Section: Surfactant Industry and Problem Identificationmentioning
confidence: 99%
“…The toxicity of the BS producing strain can be tested in the Galleria mellonella model. The Galleria model was used to test the pathogenicity in rhamnolipid BS producing strains and it was found that B. thailandensis was significantly less pathogenic than P. aeruginosa (Irorere et al 2018 ) and that a marine Pseudomonad was also non-pathogenic (Twigg et al 2018 ).…”
Section: Recommendation and Conclusionmentioning
confidence: 99%